HUBUNGAN KONDISI LINGKUNGAN TERHADAP KEANEKARAGAMAN JENIS IKAN DI SUNGAI LAWE ALAS KECAMATAN DARUL HASANAH KABUPATEN ACEH TENGGARA - Sipa Auliana; Andika Putriningtias; Teuku Fadlon Haser (Bajang Institute, 2024)
The Lawe Alas River is one of the longest rivers in Sumatra. This river has its headwaters in Southeast Aceh Regency and empties into Aceh Singkil Regency, has characteristics of fast currents with sandy and rocky bottom substrates. The diversity and distribution of fish are influenced by several aquatic environmental factors which can be used as bioindicators of water quality. The aim of this research is to analyze the level of fish diversity and analyze the influence of environmental conditions on the diversity of fish species in the Lawe Alas River, Darul Hasanah District, Southeast Aceh Regency. The fish species found from the three stations are tilapia fish (Oreochromis mossambicus), tawes fish (Barbodes gonionotus), broomstick fish (Hypostosmus sp), Jurung fish (Tor tambroides), runny fish (Nemacheilus chrysolaimus). The diversity index at station II is 1.58%, the uniformity index at station II is 1.0 and the dominance index at station II is 0.25. Based on the results obtained in the field, the diversity index, uniformity index and dominance index were highest at station II